Let's analyze Suzie's steps to determine if she solved the equation \(9x - 5 = 14(16x + 60)\) correctly.
Starting with the original equation: \[ 9x - 5 = 14(16x + 60) \]
- Distribute \(14\) on the right side: \[ 9x - 5 = 14 \cdot 16x + 14 \cdot 60 \] \[ 9x - 5 = 224x + 840 \]
So, Step 1 contains a mistake. Suzie incorrectly distributed \( \frac{1}{4} \) instead of \(14\). The correct equation after distributing is: \[ 9x - 5 = 224x + 840 \]
-
The next steps would involve moving terms: Subtract \(224x\) from both sides: \[ 9x - 224x - 5 = 840 \] This simplifies to: \[ -215x - 5 = 840 \]
-
Adding \(5\) to both sides: \[ -215x = 845 \]
-
Dividing by \(-215\): \[ x = -\frac{845}{215} \]
We can simplify that fraction, but it will not yield \(x = 13\).
Therefore, Suzie made a mistake in Step 1 where she incorrectly distributed the \(14\). The correct distribution should have been \(14 \cdot 16x + 14 \cdot 60\).
The correct response is: Suzie made a mistake on Step 1 - she should have distributed the \(14\) to \(16x\) and \(60\) as well.